Bioavailability of suppository acetaminophen in healthy and hospitalized ill dogs. Issue 5 (13th May 2018) - Sikina, E. R.; Bach, J. F.; Lin, Z.; Gehring, R.; KuKanich, B.
Abstract : To determine the plasma pharmacokinetics of suppository acetaminophen (APAP) in healthy dogs and clinically ill dogs. This prospective study used six healthy client‐owned and 20 clinically ill hospitalized dogs. The healthy dogs were randomized by coin flip to receive APAP orally or as a suppository in crossover study design. Blood samples were collected up to 10 hr after APAP dosing. The hospitalized dogs were administered APAP as a suppository, and blood collected at 2 and 6 hr after dosing. Plasma samples were analyzed by ultra‐performance liquid chromatography with triple quadrupole mass spectrometry. In healthy dogs, oral APAP maximal concentration (CMAX =2.69 μg/ml) was reached quickly (TMAX =1.04 hr) and eliminated rapidly ( T1/2 = 1.81 hr). Suppository APAP was rapidly, but variably absorbed (CMAX =0.52 μg/ml TMAX =0.67 hr) and eliminated (T1/2 = 3.21 hr). The relative (to oral) fraction of the suppository dose absorbed was 30% (range <1%–67%). In hospitalized ill dogs, the suppository APAP mean plasma concentration at 2 hr and 6 hr was 1.317 μg/ml and 0.283 μg/ml. Nonlinear mixed‐effects modeling did not identify significant covariates affecting variability and was similar to noncompartmental results. Results supported that oral and suppository acetaminophen in healthy and clinical dogs did not reach or sustain concentrations associated with efficacy. Further studies performed on different doses are needed.